Trauma-Informed Practices in Schools: A Narrative Literature Review - Record-Lemon, Rosalynn M.; Buchanan, Marla J. (Canadian Journal of Counselling and Psychotherapy, 2017)
In Canada, the influx of immigrant and refugee children from war-torn countries and the current rate of natural disasters highlight that it is time to examine our preparation within schools to address childhood traumatic events. However, there is a scarcity of empirical knowledge regarding effective trauma-informed practices (TIPs) with children in Canadian schools. The purpose of this narrative literature review is to examine the existing Canadian and international research regarding TIPs in schools. Themes noted in the literature are discussed, including research trends, strengths and gaps, and implications for future research regarding TIPs.